2018
DOI: 10.1038/s41433-018-0157-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of serum cytokine profile among patients with tubercular multifocal serpiginoid choroiditis: a pilot study

Abstract: Baseline and serial levels of inflammatory serum cytokines may help in predicting the response to ATT and corticosteroids in TB MSC. Patients with paradoxical worsening may show rise in pro-inflammatory cytokines after initiation of ATT indicating higher bacillary load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Paradoxical worsening can be predicted by various imaging biomarkers including optical coherence tomography angiography (OCTA) and inflammatory markers from the vitreous such as interleukins and tumor necrosis factor. 8,22 Studies have shown that early detection/prediction of paradoxical worsening can prevent permanent choriocapillaris/photoreceptor atrophy and help in superior visual outcomes 8,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical worsening can be predicted by various imaging biomarkers including optical coherence tomography angiography (OCTA) and inflammatory markers from the vitreous such as interleukins and tumor necrosis factor. 8,22 Studies have shown that early detection/prediction of paradoxical worsening can prevent permanent choriocapillaris/photoreceptor atrophy and help in superior visual outcomes 8,22 .…”
Section: Discussionmentioning
confidence: 99%
“…In MSC, the serum cytokine levels were studied at baseline and over a longitudinal follow up in patients who received oral corticosteroids and anti-tubercular therapy (ATT) [57]. Of 12 patients, four developed paradoxical worsening (PW) of choroiditis lesions.…”
Section: Tagirasa Et Al Identified Autoreactive T Cells In Eyesmentioning
confidence: 99%
“…The study concluded that patients with paradoxical worsening in TB-related uveitis may show a heightened immune response with higher baseline IL-10 values, early rising levels of interferon- ϒ (IFN-ϒ), progressive increase in transforming growth factor-β (TGF-β), and rising levels of TNF-α after initiation of ATT and corticosteroids. Patients with high IL-10 values have low bacilli clearance rates and more chance of persistence of infection [28]. Further, MTB is capable of stimulating the release of IL-10.…”
Section: Introductionmentioning
confidence: 99%